Photoreversible control over ionic conductivity of coumarin-containing poly(ionic liquid)-based solid electrolyte - Wangjie Xu; Ming Zhang; Yijun Chen; Qinghua Tian; Xianjing Zhou; Li Zhang; Xinping Wang; Wei Zhang (eXPRESS Polymer Letters, 2023)
Poly(ionic liquid)s (PILs) are promising candidates used as solid electrolytes because of their excellent electrochemical properties and improved processability. Introducing light-sensitive groups to PILs appears as an attractive strategy for developing novel smart PIL-based electronic devices. In this work, a new photoresponsive PIL-based solid electrolyte was prepared by blending PILs containing coumarin groups (COU-PILs) with polyvinylidene fluoride hexafluoropropylene. It was found that the ionic conductivity of COU-PIL solid electrolytes (COU-PIL SEs) can be reversibly modulated upon alternative 365 and 254 nm light irradiation. In particular, the COU-PIL SEs exhibit a highly reversible and repeatable manipulation of ionic conductivity with a maximum conductivity modulation of 95%. This reversible control over ionic conductivity is attributed to the photodimerization/photocleavage behavior of the coumarin groups.